Associations between the implicit needs for affiliation and power and identity development in a sample of Zambian adolescents. Issue 7 (3rd October 2022) - Hofer, Jan; Lehmann, Meike; Busch, Holger; Menon, Anitha
ABSTRACT: Research indicates that identity development is impacted by implicit motives. Because research in non-Western cultures is scarce, a sample from Zambia is examined; moreover, because previous research has exclusively focused on communal motives ( n Affiliation), agentic motives ( n Power) are taken into account additionally. We hypothesized that implicit motives relate to identity development only when adolescents report positive parenting experiences. Adolescents ( N = 407) provided information on implicit motives, perceived parenting quality, and identity in interpersonal and ideological domains. Results indicate that adolescents with positive parenting experiences make more motive-congruent identity commitments and reconsider them less (at least in the interpersonal domain). Findings open up new questions about the universality of the influence of implicit motives on identity development.